ANALISIS PENGARUH INSENTIF TERHADAP PENINGKATAN PRESTASI KERJA KARYAWAN PADA PT. BANK RIAU CABANG PEMBANTU PERAWANG - Imran Imran (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Pt. Bank Riau is a continuation of the business activities of PT. BAPERI (PT. Riau Regional Development Bank) which was established based on the Notary Deed of Syawal Sultan No. 1 dated August 2, 1961, and the permission of the Minister of Finance of the Republic of Indonesia.No. BUM 9-4-45 dated August 12, 1961. Furthermore, with the Decree of the Governor of KDH. TK.I Riau No. 51/IV/1966 April 1, 1966, it was stated that all activities of PT. BAPERI was merged into the Riau Regional Development Bank in accordance with Law Number 13 of 1962, officially the activities of the Riau Regional Development Bank began with the status as a Bank Owned by the Government of the Riau Province. Various changes and developments in the Bank's activities, and since 1975 the status of the establishment of the Riau Regional Development Bank, Decree of the Deputy Governor of Bank Indonesia No. 5/30 / KEP.DGS / 2003 dated 22 July 2003, the legal entity status of the Riau Regional Development Bank changed from a Regional Company (PD) Regional Development Bank of Riau to a Limited Liability Company (PT). Bank Pembangunan Daerah Riau was abbreviated as PT. Bank Riau as of August 1, 2003. This research aims to Analyze the Influence of the Incentive Factor on improving the work performance of employees at PT. Bank Riau, Perawang Sub-Branch. The number of research samples are all All employees of PT. Bank Riau, Perawang Sub-Branch, as many as 60 with the sampling method saturated sampling technique or census. Saturated sampling or census is a sampling technique when all members of the population are used as samples.Meanwhile, the leadership is used as the key information in this study. Research result shows The influence of incentives on increasing work performance having a significant influence and positive means that there is a strong positive relationship between incentives and increased work performance of employees of PT. Bank Riau Perawang Sub-Branch, through regression model, the incentive variables and the indicators in the study, are able to contribute to an increase in work performance by 88.36%, and the remaining 11.64% is influenced by other factors who were not examined in this study. Keywords : Human Resources Management, Incentif, Work Performance.